Exploring social determinants of health on chemotherapy-induced peripheral neuropathy severity in ovarian cancer: An integrative review - Chisom O. Odii; David E. Vance; Fiona B. A. T. Agbor; Amanda Jenkins; Ellen M. Lavoie Smith (Elsevier, 2024)
Ovarian cancer remains a significant public health concern for women despite advancements in cancer management. Despite comprising only 2.5 % of cancers in women, ovarian cancer ranks as the fifth leading cause of cancer-related deaths among women, with patients frequently receiving late diagnoses. Chemotherapy, a primary treatment, frequently causes chemotherapy-induced peripheral neuropathy (CIPN), affecting over 60 % of patients and leading to severe sensory, motor, and autonomic nerve impairments. This often necessitates dosage reduction or discontinuation of treatment, thereby increasing mortality. While CIPN's impact on patients is well-documented, there is a paucity of knowledge of how structural and intermediary social determinants of health factors (SDOH), such as socioeconomic and political context, material circumstances such as living and walking conditions, area deprivation, and food availability, affect CIPN severity. The aim of this article was to explore the association between various SDOH and CIPN severity in ovarian cancer, identifying potential research gaps and future research directions. This article seeks to inform targeted interventions to mitigate CIPN's impact by elucidating these associations.